Exploring Geovisualization Symbology for Landscape Genetics. Issue 2 (9th October 2012) - Aoidh, Eoin Mac; Martinsohn, Jann Th.; Maes, Gregory E.; Cariani, Alessia; Nielsen, Einar E.
Abstract Landscape genetics, which considers genetic population structure in the context of spatially referenced parameters in the surrounding landscape, has been shown to be extremely useful for wildlife management. Unfortunately its widespread uptake beyond the research community is hampered due to a lack of effective communication of usable information in a suitable format for application by stakeholders such as wildlife regulators or managers. To improve the communication of suitable information, geovisualization of results should be facilitated in a comprehensible format for stakeholders without GIS or genetic expertise. While specialist applications exist, alternative accessible solutions do not provide adequate support for the visualization of multi‐attribute spatially referenced genetic population structure information. As a solution, we document our exploration for an appropriate symbology to communicate landscape genetic information through an accessible, web‐based interface. A full problem description, review of available technologies, development rationale, and discussion of the symbology exploration are provided.